Immunohistochemical studies on the distribution and the function of the d-galactose-specific lectins in the sponge Axinella polypoides (Schmidt) - Bretting, H.; Jacobs, G.; Donadey, C.; Vacelet, J. (Cell and Tissue Research, 1983)
The distribution of the two d-galactose-specific lectins within the sponge tissue of Axinella polypoides was studied by autoradiography and by an immunohistochemical method on paraplast- and cryosections. Both techniques revealed that the lectins are stored inside the vesicles of the spherulous cells. All spherulous cells, regardless of their appearance in the different types of tissue contained the lectins. Antibodies were purified from an antiserum that reacted with both lectin I and lectin II and from the same antiserum rendered monospecific for lectin I. The purified antibodies were used to demonstrate that lectin II is predominantly present in spherulous cells with small vesicles, and lectin I in those with large vesicles. Electron-microscopic studies revealed that the spherulous cells with small vesicles are derived from archaeocytes and transformed into spherulous cells with large vesicles, a process accompanied by the conversion of lectin II to lectin I. Histological investigations showed that the tips of the bush-like, branched sponge lack the central axis, a spongin fiber network that provides support and stability to the sponge tissue. However, the missing spongin network is already preformed by cell bundles that ultimately produce the numerous fiber strands of the central axis. These bundles are composed exclusively of spindle-shaped cells and the spherulous cells. Other areas where production of spongin fibers is expected are also enriched with spherulous cells. These findings and the reaction of lectin-specific antibodies with the spongin fibers indicate that spherulous cells, and thus the lectins, are involved in synthesis of spongin fiber. Sponges lacking spongin fibers, e.g. Aaptos aaptos and Geodia cydonium, produce lectins with different carbohydrate specificity and possess large numbers of spherulous cells.